La celebrazione dei 1700 anni di Nicea in alcune pubblicazioni recenti$lLinee di tendenza di una rinnovata ricezione - Cozzi, Alberto (Teologia, 2025)
Recent publications marking the anniversary of Nicaea recover its significance and overall importance for the life of the Church, rediscovering its exemplary and unique value. In particular, four dimensions of the "event of Wisdom" that took place in Nicaea are analysed: its real historical significance; its repercussions on the life of the Church (liturgy, preaching, prayer); its challenges to theological work; its impact on cultures and interculturality. The dominant image is that of a musical score to be continually reinterpreted, so that it manifests all its power and truth in the performance that actualises its intention.